The impact of hosting refugees on the intra-household allocation of tasks: A gender perspective - Isabel Ruiz; Carlos Vargas-Silva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper examines whether the presence of refugees alters the intra-household allocation of tasks across genders in the hosting population. Using panel data (pre- and post-refugee inflow) from Kagera, a rural region of Tanzania, we find that the refugee shock led to women being less likely to engage in employment outside the household and more likely to engage in household chores relative to men. This is probably the result of the environmental degradation that accompanied the arrival of refugees and the additional competition for natural resources such as wood and water. However, the results differ by (pre-shock) literacy and maths skill. For women who could read and perform simple written mathematical operations the refugee shock resulted in a higher likelihood of engaging in outside employment. On the other hand, higher exposure to the refugee shock resulted in illiterate women being more likely to engage in farming and household chores.
Keywords: F22; J16; J61; 330; forced migration; time use; labour markets; gender; Tanzania